2001
DOI: 10.2307/2679797
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Food and the Population Dynamics of Arvicoline Rodents

Abstract: Availability of food may play a number of different dynamical roles in rodent-vegetation systems. Consideration of a suite of rodent-vegetation models, ranging from very simple ones to a model of medium complexity tailored to a specific system (brown lemmings at Point Barrow, Alaska, USA), suggested several general principles. If vegetation grows logistically following an herbivory event (a standard assumption of previously advanced models for herbivore-plant interactions), then almost any biologically reasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
142
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(146 citation statements)
references
References 30 publications
3
142
0
1
Order By: Relevance
“…Previously, many studies have focused on predatorvole interactions as the prime mechanism determining vole cycles (Hansson 1987;Henttonen et al 1987;Hanski et al 1993;Klemola et al 2000a). However, more recent evidence has suggested that changes in environment, including reductions in food quality, may also play a significant role (Agrell et al 1995;Turchin & Batzli 2001;Ergon et al 2001). Some aspects of food quality have been measured with respect to vole population growth (Agrell et al 1995;Klemola et al 2000a), but no studies have examined the effects of silica, the principal defence in their food plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, many studies have focused on predatorvole interactions as the prime mechanism determining vole cycles (Hansson 1987;Henttonen et al 1987;Hanski et al 1993;Klemola et al 2000a). However, more recent evidence has suggested that changes in environment, including reductions in food quality, may also play a significant role (Agrell et al 1995;Turchin & Batzli 2001;Ergon et al 2001). Some aspects of food quality have been measured with respect to vole population growth (Agrell et al 1995;Klemola et al 2000a), but no studies have examined the effects of silica, the principal defence in their food plants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore in voles, food quality has the potential to dictate the time taken to reach sexual maturity and the onset of breeding each year (Krebs & Myers 1974;Ergon et al 2001). There has been considerable interest in the factors influencing the growth rates and reproductive output in voles because of the impact these parameters have on individual fitness and potentially on vole population dynamics (Agrell et al 1995;Klemola et al 2000a;Turchin & Batzli 2001;Ergon et al 2001Ergon et al , 2004. Changes in food quality, if they have significant effects on vole growth and reproduction, may play a role in these population processes.…”
Section: Introductionmentioning
confidence: 99%
“…The size of many herbivore populations ultimately is constrained by per capita food supply, and for some populations, growth is immediately precluded by absolute food shortage (Solomon 1949;Sinclair 1989;Turchin and Batzli 2001;Bayliss and Choquenot 2002;Sinclair and Krebs 2002). Thus, if the dynamics of a given herbivore population are to be understood fully, the interaction between its constituents and the availability of the plants on which they subsist must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Equivalence between patterns of herbivory on treated and control sites indicated that compensatory mechanisms (i.e., competition, exportation, or immigration) counteracted any benefits of extra food accrued by hares on treated sites. Yet, changes in per capita food removal by herbivores may be missed if plant species that are used infrequently are included in biomass estimates (Haukioja et al 1983;Turchin and Batzli 2001). Thus, we also conducted a more focused analysis involving only those plant species presumed to be of greatest dietary importance to foraging hares (i.e., profitable species), assuming the tendency of hares to consume these species over winter would be most sensitive to food supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…In the language of mathematics, generating cyclic dynamics needs minimally two interacting variables (two dimensions) to induce a delayed, not immediate, density-dependent feedback on the population growth rate (Begon et al 2006). Two main classes of mechanisms have been traditionally proposed to explain this delayed feedback on the population growth rate: exogenous mechanisms involving species interactions with specialist predators (Turchin & Hanski 1997;Kendall et al 1999;Murdoch et al 2002;Turchin 2003), parasites (Redpath et al 2006) and food resources (both quantity and quality ;Keith 1990;Turchin & Batzli 2001), and endogenous mechanisms including changes in individual quality transmitted by maternal effects (Ginzburg & Taneyhill 1994), territoriality (Matthiopolous et al 2002) and genetics (Chitty 1960). The overriding historical influence of the LotkaVolterra predator-prey equations has contributed to the notion that complex dynamics may only result from interspecific interactions.…”
Section: Introductionmentioning
confidence: 99%